Corporate Social Responsibility – Firm Performance – Corporate Social Responsibility Loop: The Role Of Assurance, Reputation And Industry Type - Tanggamani, Vani (2018)
This study explores the loop concept of corporate social responsiblity practices (CSR) of the previous year, firm financial performance of the current year and CSR practice in subsequent year. Based on two sources of theory, the Stakeholder Theory explains the relationship between previous CSR practices with current firm financial performance while Slack Resources explains the relationship between current firm financial performance with future CSR practices. This study employed a quantitative research method based on content analysis of the firms’ annual report for three years, 2013 (previous year), 2014 (current year) and 2015 (future year). A total of 200 firms listed in Bursa Malaysia was selected in this study using stratified random sampling technique.